Serum Albumin and Uric Acid Levels Among Hypertensive Patients in Northwest Ethiopia: A Comparative Cross‐Sectional Study - Arega Zenaw; Belete Biadgo; Getnet Fetene; Biruktawit Abebe Assmamaw; Hana Yohanns; Adane Derso; Sintayehu Admas; Abrham Azanaw; Lyusira Marelign; Yonatan Kindie; Abebe Yenesew (Health Science Reports, 2026)
ABSTRACT Background and Aims Hypertension is a long‐term condition marked by consistently high arterial blood pressure. Hypertensive patients often experience altered serum albumin and uric acid, attributed to factors like inflammation, kidney damage, and the activation of the renin angiotensin aldosterone system. However, localized evidence regarding these biomarkers remains scarce within the Ethiopian context. This study aimed to assess the level of serum albumin and uric acid among hypertensive patients. Methods A comparative cross‐sectional study was conducted from March 1 to May 30, 2025, involving 232 study participants selected using systematic random sampling. Of these, 116 were patients with hypertensive and 116 were normotensives. Sociodemographic, behavioral, and clinical data were measured by structured questionnaires. Serum albumin and uric acid levels were measured by spectrophotometric principle. Data were analyzed using SPSS version 25 software. Descriptive statistics, independent t ‐tests, and binary logistic regression were performed with significance set at p < 0.05. Results The mean age of the study participants was 46 ± 11.4 and 45 ± 11.6 for the case and control groups. There was a statistically significant difference in mean serum albumin and uric acid levels between the case and control groups. The prevalence of hypoalbuminemia and hyperuricemia among hypertensive patients were 25.9% (95% CI: 18.2%, 34.8%) and 23.3% (95% CI: 15.9%, 32%), respectively. Multivariable logistic regression showed hypertensive patients with albuminuria had 3.3 and 16.1 odds of developing hypoalbuminemia and hyperuricemia. Conclusion This study demonstrates that the prevalence of hypoalbuminemia and hyperuricemia was higher in hypertensive patients than the controls. Albuminuria was a significant predictor of hypoalbuminemia and hyperuricemia. This underscores the potential metabolic alterations that may be associated with hypertension. Thus, it is important to monitor these parameters in hypertensive individuals.